Ligas multicomponentes do sistema Ti33Cr37V30-xNbx (X: 0, 5, 10 e 15) para armazenamento de hidrogênio - Silva, Wágner Batista (Universidade Federal de São Carlos, 2021)
The use of metal hydrides is a competitive alternative to hydrogen storage in liquid or gaseous states. Metallic alloys based on the TiCrV system have attractive hydrogen storage characteristics compared with those of the different groups of alloys already studied. Niobium is an element of great interest in a quaternary composition when included in alloys of the TiCrV system because of its high capacity to form compounds with hydrogen, its abundance, and its low cost in the Brazilian market. In this study, the Ti33Cr37V30-xNbx (x = 0, 5, 10, and 15) cast alloys had their gravimetric and volumetric hydrogen storage capacities analyzed when processed by machining (turning). Produced by arc fusion, the alloys showed formation of a single phase, with body-centered cubic (BCC) structure. Scanning electron microscopy (SEM) images evidenced that the chips resulting from turning presented serrated patterns with two distinct surfaces: one with elongated teeth and, oppositely, one with a flattened morphology. After the absorption/desorption cycles, X-ray diffraction (XRD) identified the formation of hydrides with crystalline face-centered cubic (FCC) and CCC structures. After the fragmented materials were cycled five times, the Ti33Cr37V15Nb15 alloy presented the best storage performance in relation to the amount of hydrogen absorbed, obtaining a 1.7 hydrogen-metal ratio (H/M). The fragmentation process became viable because of the shorter time spent to process the Ti33Cr37V30-xNbx (x = 0, 5, 10 and 15) cast alloys, simultaneously with its smaller reactivity with the external environment, when compared with the high-energy ball milling (HEBM) process. Kinetic curves showed that reducing the concentration of vanadium at the expense of niobium is viable, with higher H/M values.
Multicomponent alloys of the system Ti33Cr37V30−xNbx (x: 0, 5, 10 and 15) for hydrogen storage
Keywords: Ligas multicomponentes; Sistema TiCrVNb; Armazenamento de hidrogênio; Multicomponent alloys; TiCrVNb system; Hydrogen storage; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO